Communication Intervention Implementation via Telepractice Parent Coaching: Child Outcomes and Correlations. Issue 1 (March 2022) - Wattanawongwan, Sanikan; Ganz, J. B.; Pierson, Lauren M.; Yllades, Valeria; Liao, Ching-Yi; Ura, Sarah K.
Individuals with autism spectrum disorder (ASD) have deficits in social and communication skills that can cause problems such as difficulty interacting with others and challenging behaviors. Research has demonstrated the effectiveness of parents as intervention implementers to improve children's communication skills. We evaluated the effects of a telepractice parent coaching communication intervention on communication skills of children with ASD utilizing a multiple probe design across participants. Parents applied strategies learned with their child, targeting communication skills, such as asking opinion-oriented questions or using augmentative and alternative communication to request items. Results indicated improvement in children's communicative behaviors and a significant correlation between parent implementation of intervention elements and children behaviors. Effect size results for the participants indicated strong effects consistent with visually inspected data.